Changes Of Future Education Model - Ro'ifah Ro'ifah (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2019)
Technology is rapidly changing the world around us. It develops so fast that it can answer almost every person question instantly. Many drivers such as global connectivity, smart machines, and new media are reshaping how people think, what shapes, and how people learn and develop skills in the future. Many people feel disturbed that technology will replace human intelligence. In fact, there are concerns for some teachers that there will be no students teaching again in the future because technology might take over many of the tasks and abilities teachers have taught students for decades. But what does this mean for future education? When we begin to rely more and more on computers to answer our questions, it will make us lose the ability to answer ourselves. Education will never disappear. It will only take a different model. Slowly but surely, all levels of education will change the educational model. There are eight things that will shape the future of education for the next twenty years; diverse times and places, personalized learning, free choice, project based, field experience, changes in completed exams, student ownership, and more important guidance.